2016
DOI: 10.1073/pnas.1519157113
|View full text |Cite
|
Sign up to set email alerts
|

Economic irrationality is optimal during noisy decision making

Abstract: According to normative theories, reward-maximizing agents should have consistent preferences. Thus, when faced with alternatives A, B, and C, an individual preferring A to B and B to C should prefer A to C. However, it has been widely argued that humans can incur losses by violating this axiom of transitivity, despite strong evolutionary pressure for reward-maximizing choices. Here, adopting a biologically plausible computational framework, we show that intransitive (and thus economically irrational) choices p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
190
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(206 citation statements)
references
References 41 publications
12
190
4
Order By: Relevance
“…However, it draws from other models, formulated in various domains. In terms of computational assumptions, our model is similar to neuroscientific models explaining option selection in value-based choice (Louie et al, 2011, 2013; Chau et al, 2014; Hunt et al, 2014; Tsetsos et al, 2016). Our model shares computational assumptions with models by Hunt et al (2014) and Louie et al (2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it draws from other models, formulated in various domains. In terms of computational assumptions, our model is similar to neuroscientific models explaining option selection in value-based choice (Louie et al, 2011, 2013; Chau et al, 2014; Hunt et al, 2014; Tsetsos et al, 2016). Our model shares computational assumptions with models by Hunt et al (2014) and Louie et al (2013).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we think it is time to build models of decision strategy selection that can provide predictions that go beyond behavior and that can be tested in neurophysiological studies. The need to develop such models is also underlined by the fact that several neurophysiological models of multi-attribute choice already exist (Louie et al, 2013; Chau et al, 2014; Hunt et al, 2014; Tsetsos et al, 2016). These models are relevant here, because they stress the importance of brain-wide computational processes as determinants of choice—particularly, the divisive normalization, hierarchical inhibition and gain control processes.…”
Section: Toward a Neurocognitive Model Of Decision Strategy Selectionmentioning
confidence: 99%
“…In PNAS, Tsetsos et al (1) report intransitive preferences consistent with selective integration (SI) theory. The Condorcet paradox warns that aggregating transitive (rational) preferences readily creates intransitive (irrational) collective preferences (2).…”
mentioning
confidence: 90%
“…Therefore, any study reporting intransitive behavior must guard against aggregation artifacts (3). In experiments 1-3, Tsetsos et al (1) reported significant evidence against a null and in favor of FW:P AB > 1=2 and P BC > 1=2 and P CA > 1=2 (Fig. 1), in data aggregated across participants to infer intransitive "frequent-winner" (FW) effects for "cyclic trials."…”
mentioning
confidence: 99%
See 1 more Smart Citation